Thoracic complications of pancreatitis. Issue 1 (22nd October 2018) - Kumar, Prem; Gupta, Pankaj; Rana, Surinder
Abstract : Acute pancreatitis in its severe form may lead to systemic inflammatory response syndrome and multisystem organ dysfunction. Acute lung injury is an important cause of mortality in the setting of severe acute pancreatitis. Besides lung involvement, acute and chronic pancreatitis may also lead to the involvement of other thoracic compartments, including mediastinum, pleura, and vascular structures. These manifestations are an important cause of morbidity and may pose diagnostic and therapeutic challenges. These manifestations have not been discussed in detail in the available literature. In this review, we discuss the thoracic complications of pancreatitis, including lung, pleural, mediastinal, and vascular manifestations. Abstract : Acute lung injury is an important cause of mortality in the setting of severe acute pancreatitis. Besides lung involvement, acute and chronic pancreatitis may also lead to the involvement of other thoracic compartments including mediastinum, pleura, and vascular structures. In this review, we discuss the thoracic complications of pancreatitis including lung, pleural, mediastinal and vascular manifestations.